2019
DOI: 10.52962/ipjaf.2019.3.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Exploration Disclosures of Internal Control as the Impact of Earnings Quality and Audit Committee

Abstract: Information disclosure carried out by management as an appointed agent is increasing in importance and hence, a source of concerns to users.  It is widely believed that information received by the stakeholders should be appropriate and sufficient for useful decision making, especially in the era of the Fourth industrial revolution. An appropriate and sufficient disclosure in the Annual report indicates a reflection of the effective implementation of the company's operational, strategic, financial and complianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…Applying an accounting standard relates to its importance in disclosing accounting information that describes financial performance in financial reporting. The application of accounting standards also aims to obtain good-quality financial reports (Pangaribuan et al, 2019). Previously (Ewert and Wagenhofer, 2016) say that although many have found that the use of accounting standards can increase disclosure and make information more symmetrical, the reality is that existing accounting standards tend to have the opposite effect.…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…Applying an accounting standard relates to its importance in disclosing accounting information that describes financial performance in financial reporting. The application of accounting standards also aims to obtain good-quality financial reports (Pangaribuan et al, 2019). Previously (Ewert and Wagenhofer, 2016) say that although many have found that the use of accounting standards can increase disclosure and make information more symmetrical, the reality is that existing accounting standards tend to have the opposite effect.…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…The birth of GAS has changed the pattern of government financial management in Indonesia. Agbodjo et al, (2021); Miyauch & Sanada (2019) added that these standards serve as guidelines for preparing quality government and non-government financial reports (Pangaribuan et al, 2019) had an impact on increasing voluntary disclosure (Pangaribuan et al, 2022) and provided benefits to stakeholders (Dumisani, 2019). Anggadini et al, (2023); Pangaribuan et al, (2023) Supriyanto et al, (2023; Costa et al, (2022); Dahana & Purnomowati (2022) Yusrina et al, (2017) argued that the use of accounting standards significantly improve the quality of financial reports.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical framework 2.1 Historical and legal landmarks of internal control Internal control integrates the scope of the control function and, within the organization, occupies a level of extreme importance that affects objectives, plans, information, processes, systems, activities, functions, projects and initiatives (Montenegro, Oliveira, & Lopes, 2017). The internal control system comprises a process that aims to achieve operational effectiveness and efficiency, reliability, criteria compliance and compliance with laws and regulations (Pangaribuan, Donni, Popoola, & Sihombing, 2019).…”
Section: Introductionmentioning
confidence: 99%